PERILAKU BELAJAR SISWA PENAMBANG TIMAH INKONVENSIONAL DI SMP NEGERI 10 PANGKALPINANG - Defrizal Defrizal (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This research has goal to find out the study behaviors of inconventional tin mining students at SMP Negeri 10 Pangkalpinang. Kind of this research is  Qualitative research. Informants in this research were the headmaster, the mining  students where informant taking technique by using Purposive  sampling. The technique of collecting the data by using means of observation, interview  and documentation. Technique of analizing the data used are Milles and hubberman by using data reduction, data display, data interpretation and conclusion. The results showed inconventional tin mining impact on students' learning behavior in the tin miners in teaching and learning in the classroom, consolidation behavior, the behavior of writing, reading, working on assignments and behavior in the exam / test.Keywords: Learning, Student Behavior, Miners Lead Unconventional